2021
DOI: 10.1007/s00726-021-02954-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative testicular injury: effect of l-leucine on redox, cholinergic and purinergic dysfunctions, and dysregulated metabolic pathways

Abstract: The antioxidant and anti-proinflammatory activities of l-leucine were investigated on oxidative testicular injury, ex vivo. In vitro analysis revealed l-leucine to be a potent scavenger of free radicals, while inhibiting acetylcholinesterase activity. Oxidative injury was induced in testicular tissues using FeSO 4 . Treatment with l-leucine led to depletion of oxidativeinduced elevated levels of NO, MDA, and myeloperoxidase activity, with concomitant elevation of reduced glutathione and non-protein thiol level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 75 publications
4
13
0
Order By: Relevance
“…The suppressed acetylcholinesterase activity in following treatment with strawberry fruits, therefore, indicates an improved cellular availability of acetylcholine for normal testicular physiology. This corroborates reports on the efficacy of acetylcholinesterase inhibitors for treating and managing testicular dysfunctions (Erukainure, Atolani, et al., 2021; Uzun et al., 2009). Strawberries have been reported previously for their ability to inhibit acetylcholinesterase activity (Erukainure, Salau, Oyenihi, et al., 2020; Hwang et al., 2019), and can also be attributed to the HPLC‐identified phenolics (Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…The suppressed acetylcholinesterase activity in following treatment with strawberry fruits, therefore, indicates an improved cellular availability of acetylcholine for normal testicular physiology. This corroborates reports on the efficacy of acetylcholinesterase inhibitors for treating and managing testicular dysfunctions (Erukainure, Atolani, et al., 2021; Uzun et al., 2009). Strawberries have been reported previously for their ability to inhibit acetylcholinesterase activity (Erukainure, Salau, Oyenihi, et al., 2020; Hwang et al., 2019), and can also be attributed to the HPLC‐identified phenolics (Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown the involvement of oxidative stress on enhanced acetylcholinesterase activity (Rodriguez‐Diaz et al., 2011). The elevated ACTh activity (Figure 4) on the induction of oxidative testicular injury may have emanated from oxidative stress in the testicular tissues, as described in previous studies (Erukainure, Atolani et al., 2021; Erukainure et al., 2021). Additionally, the negative binding energies of the infusion phytochemicals with ACTh protein (Table 2) may also portray its ACTh inhibitory properties.…”
Section: Discussionsupporting
confidence: 70%
“…In prostate cancer cells, elevated ATPase activity was reported to enhance motility and invasion (Michel et al., 2013). The high ATPase activity in the untreated (Figure 5) may indicate acid/base imbalance in testicular tissue owing to the oxidative onslaught as well as depleted levels of ATP (Erukainure, Atolani et al., 2021). Moreover, spermatozoa survival and functionality critically rely on the maintenance of testis tubule pH within the physiology range (Nishigaki et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, clinically, there are infertile patients who have improved semen quality by taking compound amino acid capsules. Also, a reduction in the levels of leucine will result in a reduction in antioxidant and anti-inflammatory ability 27 . Furthermore, a reduction of glutamic acid will lead to a reduction in acid resistance, thus making sperm vulnerable to damage 28 .…”
Section: Discussionmentioning
confidence: 99%